Clinical outcomes of pterygium surgery over a ten-year period: a review of recurrence and complication rates - Sharlene I. Noguera; Katherine S. Aniana Nicanor; Robert Edward T. Ang; Emerson M. Cruz (BMC Ophthalmology)
Abstract Purpose This study described the clinical profile and post-operative outcomes of patients who underwent pterygium surgery at an ambulatory eye center in the Philippines over a ten-year period. Methods This retrospective study analyzed medical records of 462 eyes from 408 patients who underwent pterygium surgery by a single surgeon between February 2013 and August 2023. The study examined the clinical characteristics of patients with pterygium and evaluated the recurrence rates of three treatment methods: pterygium excision with conjunctival autograft (CAG), pterygium excision with dehydrated amniotic membrane graft (DAG), and primary excision with mitomycin C application. Descriptive statistics were used for analysis of patient demographics, clinical profile, and postoperative outcomes. Results The mean patient age was 48 years (range 17–81), with a slight male predominance (57%). Nasal pterygium was the most common type (72%), followed by bipolar (8%) and temporal (3%) pterygium. Most cases were primary (81%), with T2G1 being the most common grading. Conjunctival autograft was the predominant surgical technique (94%), followed by dehydrated amniotic membrane graft (5%) and primary excision with mitomycin C application (1%). The overall recurrence rate was 1%, with conjunctival autograft showing the lowest rate, compared to dehydrated amniotic membrane graft and primary excision with mitomycin C. The complication rate was 4.5%, primarily minor findings such as conjunctival granuloma, wound dehiscence, and residual pterygium. Conclusion Most pterygium cases presented as primary and in the nasal area with T2G1 grading. This study supports conjunctival autograft as the preferred surgical technique for pterygium because of the low recurrence and complication rates.